Afternoon of the elves - Lisle, Janet Taylor (Orchard Books, 1989)
As Hilary works in the miniature village, allegedly built by elves, in Sara-Kate's backyard, she becomes more and more curious about Sara Kate's real life inside her big, gloomy house with her mysterious, silent mother.